2010
DOI: 10.5194/amt-3-1217-2010
|View full text |Cite
|
Sign up to set email alerts
|

Reference Quality Upper-Air Measurements: guidance for developing GRUAN data products

Abstract: Abstract. The accurate monitoring of climate change imposes strict requirements upon observing systems, in particular regarding measurement accuracy and long-term stability. Currently available data records of the essential climate variables (temperature-T , geopotential-p, humidity-RH, wind, and cloud properties) in the upper-air generally fail to fulfil such requirements. This raises serious issues about the ability to detect, quantify and understand recent climate changes and their causes. GCOS is currently… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
157
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(174 citation statements)
references
References 13 publications
0
157
0
Order By: Relevance
“…In addition to these principles, the Global Climate Observing System 2010 (GCOS, 2010) defined observation requirements for essential climate variables, such as upper-air tropospheric and stratospheric temperature. The requirements for the precision and resolution of temperature profiles are less than 0.5 K root-mean-square value, 500 and 0.5 km horizontal and vertical resolutions, respectively, in the upper troposphere and 1.5 km vertical resolution in the lower stratosphere (Immler et al, 2010;Steiner et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these principles, the Global Climate Observing System 2010 (GCOS, 2010) defined observation requirements for essential climate variables, such as upper-air tropospheric and stratospheric temperature. The requirements for the precision and resolution of temperature profiles are less than 0.5 K root-mean-square value, 500 and 0.5 km horizontal and vertical resolutions, respectively, in the upper troposphere and 1.5 km vertical resolution in the lower stratosphere (Immler et al, 2010;Steiner et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For long-term climate observations using frequently changing instruments this stability test prior to launch is essential to gain confidence in the data set (Immler et al, 2010). Although we did not start this test when the older instruments described in Sect.…”
Section: Ground Checkmentioning
confidence: 99%
“…Although they are recognized by many as reference instruments, we refer to the rigorous definition of what constitutes a reference observation given recently by Immler et al (2010). This paper defines reference-quality atmospheric observations as such, which are based on traceability, a detailed analysis of the uncertainty budget, and a detailed knowledge of the calibration procedures and data processing algorithms that are required for determining the uncertainty of each individual data point.…”
Section: Introductionmentioning
confidence: 99%
“…-The measurements are traceable through an unbroken processing chain (in which the uncertainty arising in each step has been rigorously quantified) to SI units, common reference points defined by BIPM or community recognised standards (ideally recognised by the National Measurement Institute), using best practices documented in the accessible literature (Immler et al, 2010). Dirksen et al (2014) provide an example of the steps required to deliver such a product.…”
Section: Reference-observing Networkmentioning
confidence: 99%
“…A key step to achieving this is to identify, in as unambiguous a manner as possible, those non-satellite measurements that are suitable for such an application. These reference observations must be sufficiently well characterised (JGCM, 2008;Immler et al, 2010;WMO/BIPM, 2010), so that if a difference is found in the satellite data being compared, after accounting for inevitable co-location mismatch effects, we can be confident that the difference arises from the satellite and not from the comparator.…”
Section: Introductionmentioning
confidence: 99%